Group A Streptococcus secreted esterase hydrolyzes platelet-activating factor to impede neutrophil recruitment and facilitate innate immune evasion. - Mengyao Liu; Hui Zhu; Jinquan Li; Cristiana C Garcia; Wenchao Feng; Liliya N Kirpotina; Jonathan Hilmer; Luciana P Tavares; Arthur W Layton; Mark T Quinn; Brian Bothner; Mauro M Teixeira; et al. (PLoS Pathogens)
The innate immune system is the first line of host defense against invading organisms. Thus, pathogens have developed virulence mechanisms to evade the innate immune system. Here, we report a novel means for inhibition of neutrophil recruitment by Group A Streptococcus (GAS). Deletion of the secreted esterase gene (designated sse) in M1T1 GAS strains with (MGAS5005) and without (MGAS2221) a null covS mutation enhances neutrophil ingress to infection sites in the skin of mice. In trans expression of SsE in MGAS2221 reduces neutrophil recruitment and enhances skin invasion. The sse deletion mutant of MGAS5005 (Δsse(MGAS5005)) is more efficiently cleared from skin than the parent strain. SsE hydrolyzes the sn-2 ester bond of platelet-activating factor (PAF), converting biologically active PAF into inactive lyso-PAF. K(M) and k(cat) of SsE for hydrolysis of 2-thio-PAF were similar to those of the human plasma PAF acetylhydrolase. Treatment of PAF with SsE abolishes the capacity of PAF to induce activation and chemotaxis of human neutrophils. More importantly, PAF receptor-deficient mice significantly reduce neutrophil infiltration to the site of Δsse(MGAS5005) infection. These findings identify the first secreted PAF acetylhydrolase of bacterial pathogens and support a novel GAS evasion mechanism that reduces phagocyte recruitment to sites of infection by inactivating PAF, providing a new paradigm for bacterial evasion of neutrophil responses.